Management of the Implementation of Ahlussunnah Wal Jama'ah An Nahdliyah Values in Strengthening Student Character - Muhammad Yusuf; Siti Muthmainah; Eka Prasetiawati (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study examines the internalization of moderate Islamic values within the educational system as a strategic effort to shape students’ religious, tolerant, and nationalist character amid challenges of moral degradation and radicalism. The research aims to analyze the implementation of Ahlussunnah wal Jama’ah (Aswaja) An-Nahdliyah values in educational management, describe their role in strengthening student character, and explore the relevance of KH. Wahid Hasyim’s educational thought in this context. A qualitative field research approach was employed at Madrasah Aliyah Ma’arif NU 5 Sekampung, East Lampung. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that Aswaja values are systematically integrated into planning, organizing, implementation, and evaluation processes, supported by religious habituation, contextual learning, and teacher role modeling. These practices contribute significantly to the development of students’ moderate, tolerant, balanced, and patriotic character. The study concludes that Aswaja-based educational management, aligned with Wahid Hasyim’s integrative and moral-oriented thought, offers a relevant and contextual model for character education in contemporary Islamic schooling.